Analisis Implementasi Pembelajaran Online Pada Mata Pelajaran Matematika Jenjang Sekolah Dasar - Alamsyah Basri Ismail (Institute Journal and Publication Muhammadiyah University of Buton, 2024)
This study aims to analyze the implementation of online learning in mathematics subjects at the elementary school level. This research uses a qualitative method with a case study approach in several elementary schools in Indonesia. Data were collected through interviews with teachers and students, as well as direct observations of the learning process. The results show that online learning has several challenges, including limited internet access, low digital skills among students and teachers, and a lack of effective social interaction. However, several benefits were also found, such as time flexibility and more varied learning resources. This study concludes that despite some obstacles, online learning can be optimized with the right strategies, such as digital skills training for teachers and students, as well as improving technology infrastructure.